Social Media Content And Hedonic Brand Image In Eco-Friendly Fashion Start-Up - Diyah Tulipa; Andy Pratama Sulistyo; Tania Mellifan (Jurnal Manajemen, 2023)
In the internet era, as it is today, social media is an important tool for communication. Not only for personally but also for communication between companies and consumers. The study aims to determine the effect of social media advertising content and sales promotional content on purchase intention through the hedonic brand image of brand- new fashion start-up KA2N. This study employed 113 Instagram followers of KA2N. The results show that social media advertising content and media social sales promotional content have influence hedonic brand image, then in turn hedonic brand image affects purchase intention.  However, social media advertising content and social media sales promotion content does not directly influence consumer purchase intention, significantly. It means that hedonic brand image mediates the relationship between social media advertising content and social media sales promotion content with purchase intention.